Regulatory T cells in transplantation tolerance. - Waldmann, H; Graca, L; Adams, E; Fairchild, P; Cobbold, S (2005)
Our ability to harness tolerance mechanisms will have a major impact in organ transplantation if it becomes possible to minimize drug maintenance, or even wean off immunosuppressive drugs. An improved understanding of the biology of regulatory T cells will make it possible to replace current induction regimens with those favouring the vaccination and selection of T cells that prevent graft rejection. Once tolerance is established, the continuous supply of graft antigens should sustain T cell mediated regulation as the dominant mechanism preventing graft rejection.